Development of interactive multimedia on environmental pollution topics with STEM approach for junior high school students - Zusje Wiesje Merry Warouw; Elcia Romarta Purba; Widya Anjelia Tumewu; Ester Caroline Wowor; Brian Ricard Wola (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The 21st century is known as the digital age, in which teachers' and students' ability to access and utilize technology is essential. This study aims to develop feasible and practical interactive multimedia on environmental pollution topics with a STEM approach for junior high school students. The research type we use is development research using the ADDIE model. The data collection techniques used were interviews and questionnaires. The research instruments used were interview sheets and questionnaires. Quantitative and qualitative data analysis techniques were used in this study. The results showed that the validation of subject matter experts was 93%, learning media experts was 94%, and peer assessment was 94%. All three were included in the very feasible category and did not require revision. In addition, the small group evaluation obtained an average score of 4.50 with a percentage of 90%. Based on these findings, interactive multimedia on environmental pollution topics with a STEM approach for junior high school students was declared feasible and practical for science learning. The STEM-based teaching material we have successfully produced can support and answer some of today's science learning challenges.Abstrak. Abad ke-21 dikenal sebagai era digital, dimana kemampuan guru dan siswa dalam mengakses dan memanfaatkan teknologi menjadi sangat penting. Penelitian ini bertujuan untuk mengembangan multimedia interaktif berbasis STEM pada topik pencemaran lingkungan untuk siswa SMP yang layak dan praktis digunakan. Jenis penelitian yang kami gunakan adalah penelitian pengembangan menggunakan model ADDIE. Teknik pengumpulan data yang kami gunakan adalah wawancara dan kuisioner. Instrumen penelitian yang kami gunakan adalah lembar wawancara dan angket. Teknik analisis data kuantitatif dan kualitatif digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa validasi ahli materi pelajaran 93%, ahli media pembelajaran 94%, dan penilaian teman sejawat 94% yang mana ketiganya termasuk pada kategori sangat layak dan tidak memerlukan revisi. Selain itu, hasil penilaian siswa dalam small group evaluation memperoleh skor rata-rata 4.50 dengan persentase 90%. Berdasarkan temuan tersebut, multimedia interaktif berbasis STEM pada topik pencemaran lingkungan untuk siswa SMP dinyatakan layak dan praktis dimanfaatkan dalam pembelajaran IPA. Bahan ajar berbasis STEM yang berhasil kami produksi diharapkan mendukung dan menjawab sebagian tantangan pembelajaran IPA masa kini.